2015
DOI: 10.1177/0148607115595596
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐Like Peptide‐2 Alters Bile Acid Metabolism in Parenteral Nutrition–Associated Liver Disease

Abstract: GLP-2 treatment was associated with alterations in the hepatic expression of genes involved in bile acid metabolism. The transcriptomic results indicate the mechanisms at the transcriptional level acting to regulate bile acid synthesis and increase bile acid export. Differences in bile acid profiles further support a beneficial role for GLP-2 therapy in PNALD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…For the other four BA (THDCA, TCDCA, GHDCA, and GCDCA) for which authentic standards were not available, Specifically, THDCA and TCDCA were estimated using to the calibration curve of TDCA, GHDCA was estimated using the calibration curve of GUDCA, and GCDCA was estimated based on the calibration curve of GDCA. A detailed analysis of these results and the biological implications have been recently reported in a separate publication [7]. A detailed analysis of these results and the biological implications have been recently reported in a separate publication [7].…”
Section: Application To Piglet Bile Samplesmentioning
confidence: 94%
See 1 more Smart Citation
“…For the other four BA (THDCA, TCDCA, GHDCA, and GCDCA) for which authentic standards were not available, Specifically, THDCA and TCDCA were estimated using to the calibration curve of TDCA, GHDCA was estimated using the calibration curve of GUDCA, and GCDCA was estimated based on the calibration curve of GDCA. A detailed analysis of these results and the biological implications have been recently reported in a separate publication [7]. A detailed analysis of these results and the biological implications have been recently reported in a separate publication [7].…”
Section: Application To Piglet Bile Samplesmentioning
confidence: 94%
“…The most well-known biological roles of BA are in aiding digestion and absorption of fats via the formation of micelles [1]. Taking parenteral nutrition-associated liver disease (PNALD) as an example, it is a cholestatic liver disease partially caused by developmental immaturity with regards to hepatic BA metabolism and transport and currently without established pharmacological treatments [7]. Due to these important biological roles, BA metabolism is closely associated with cholesterol homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative real‐time polymerase chain reaction (qPCR) was performed on frozen liver samples. Hepatic expression of genes involved in BA synthesis: cholesterol 7‐hydroxylase (CYP7A1); BA sensing: farnesoid X receptor (FXR), small heterodimer partner (SHP); BA transporter in enterohepatic circulation: organic solute transporter alpha (OSTα); BA uptake mediator from blood into liver: Na + ‐taurocholate cotransporting polypeptide (NTCP); BA efflux mediator from liver into bile canaliculi: bile salt export pump (BSEP); BA transporter into the bile along with cholesterol: multidrug resistance–associated proteins 2 and 3 (MRP2, MRP3) were assessed as previously reported 13 (for primers see Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Bile samples collected at the time of measuring bile flow were pooled and stored at −80°C. Analysis of bile composition was undertaken using a 20‐µL bile sample with addition of 200 µL internal standard solution (GCA‐d4, 1 ppm) using a solid phase extraction method followed by a liquid chromatography/tandem mass spectrometry (LC‐MS/MS) analysis, as we have described previously, 13 with modifications (see Supplementary Table S2). Cholic acid (CA), chenodeoxycholic acid (CDCA), lithocholic acid (LCA), taurocholic acid (TCA), hyocholic acid (HCA), taurolithocholic acid (TLCA), glycolithocholic acid (GLCA), hyodeoxycholic acid (HDCA), and taurohyocholic acid (THCA) were all accurately quantified using the authentic standards.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments advancing this theory have shown that such gut and hepatoprotective signaling can be recapitulated by delivering luminal BAs in animal PN model systems . In fact, prevention of gut atrophy and an improvement in hepatic outcomes have been shown to occur on enteral administration of the BA CDCA in animals receiving PN with intact gut .…”
Section: Discussionmentioning
confidence: 99%